2010
DOI: 10.5851/kosfa.2010.30.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Extract Mixtures from Artemisia capillaris, Camellia sinensis, Schizandra chinensis, and Viscum album var. coloratum on Laying Performance, Egg quality, Blood Characteristics, and Egg Storage Stability in Laying Hens

Abstract: This study investigated the effects of three kinds of water extract mixtures each with different ratios of A. capillaris, C. sinensis, S. chinensis, and V. coloratum on laying performance, egg quality, blood characteristics, and egg storage stability in laying hens. One hundred and sixty 35-wk-old laying hens (Hy-line brown) were divided into four groups of 10 birds each replicated times four. The treatments involved a basal diet (C, control) or diets containing three kinds of water extract mixtures at 200 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Conversely, a high inclusion of A. annua leaves did not significantly increase egg weight, but dramatically decreased FCR (Baghban-Kanani et al, 2018). The inclusion of Artemisia capillaris was reported to increase egg production of laying hens (Kim et al, 2010). Positive effects on body weight gain and feed efficiency were also reported by supplementing Lactobacillus-fermented Artemisia princeps for broilers (Kim et al, 2012a).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, a high inclusion of A. annua leaves did not significantly increase egg weight, but dramatically decreased FCR (Baghban-Kanani et al, 2018). The inclusion of Artemisia capillaris was reported to increase egg production of laying hens (Kim et al, 2010). Positive effects on body weight gain and feed efficiency were also reported by supplementing Lactobacillus-fermented Artemisia princeps for broilers (Kim et al, 2012a).…”
Section: Discussionmentioning
confidence: 97%
“…There has been an increasing interest in using phytogenic feed additives (PFA) in animal feed during the last two decades (Mohammadi Gheisar & Kim, 2018). To date, many studies have reported antimicrobial, antioxidant, anti-inflammatory, and growth-promoting effects of PFA in animals (Kim et al, 2010;Abdel-Wareth & Lohakare, 2014;Qin & Hou, 2017;Abou-Elkhair et al, 2018;Mohammadi Gheisar & Kim, 2018). Phytogenic sources contain abundant phytochemicals, which have been mainly classified into three categories as carotenoids, isothiocyanates, and polyphenols, and most polyphenols are recognized as having beneficial functions (Fraser, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of adverse effects on performance traits has also been reported in broiler breeds when fed with pine ( Pinus brutia ) needle powder (10 g/kg of diet) [ 18 ] and S. chinensis powder (5, 10, or 20 g/kg of diet) [ 13 ]. Alternatively, Kim et al [ 29 ] observed that the egg production rate was significantly improved when the mixtures of Artemisia campestris ( A. campestris ), Camellia sinensis ( C. sinensis ), S. chinensis , and Viscum album var. coloratum were fed to laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Paik [ 33 ] also indicated no changes in eggshell strength, eggshell thickness, eggshell color, egg yolk, and HU when 66-wk-old Hy-line Brown hens were fed 0.2% plant extracts, including turmeric, Angelica gigas , S. chinensis , Glycyrrhiza glabra , and Levisticum officinale . On the other hand, Kim et al [ 29 ] demonstrated that HU and egg yolk color were significantly increased compared to control, but eggshell thickness, and eggshell breaking strength were not changed when a mixture of A. campestris , C. sinensis , S. chinensis , and Viscum album var. coloratum was fed to laying hens.…”
Section: Discussionmentioning
confidence: 99%